2010
DOI: 10.1038/nature09485
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the marine phosphate reservoir

Abstract: Phosphorus is a biolimiting nutrient that has an important role in regulating the burial of organic matter and the redox state of the ocean-atmosphere system. The ratio of phosphorus to iron in iron-oxide-rich sedimentary rocks can be used to track dissolved phosphate concentrations if the dissolved silica concentration of sea water is estimated. Here we present iron and phosphorus concentration ratios from distal hydrothermal sediments and iron formations through time to study the evolution of the marine phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
268
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 395 publications
(290 citation statements)
references
References 30 publications
13
268
0
1
Order By: Relevance
“…This means that there should be a large reservoir of dissolved P and Fe in the anoxic basin. This is consistent with earlier studies which proposed that anoxic P-and Fe-rich marine deep waters were a general feature of the later Neoproterozoic according to Fe speciation and P/Fe ratios in Neoproterozoic sediments (Canfield et al, 2008;Planavsky et al, 2010). In order for the P and Fe in the anoxic bottom water to reach the shallow platform, deep basin brines would have to have experienced overturn and upwelling creating ideal conditions for the Group-F carbonate precipitation.…”
Section: Brine Watersupporting
confidence: 91%
“…This means that there should be a large reservoir of dissolved P and Fe in the anoxic basin. This is consistent with earlier studies which proposed that anoxic P-and Fe-rich marine deep waters were a general feature of the later Neoproterozoic according to Fe speciation and P/Fe ratios in Neoproterozoic sediments (Canfield et al, 2008;Planavsky et al, 2010). In order for the P and Fe in the anoxic bottom water to reach the shallow platform, deep basin brines would have to have experienced overturn and upwelling creating ideal conditions for the Group-F carbonate precipitation.…”
Section: Brine Watersupporting
confidence: 91%
“…Rhenium enrichments in the Black River Dolomite are consistent with increased ocean oxygenation in the wake of the Sturtian glaciation, as suggested by Planavsky et al (2010). While Re data from the Upper Velkerri and Touirist formations may potentially reflect transiently oxygenated marine conditions, the extent to which these data represent spatiotemporal variations in the midProterozoic atmosphere-ocean redox state remains to be tested with higher-resolution Re data for stage 3.…”
Section: Constraints On the Extent Of Mid-proterozoic Ocean Anoxiamentioning
confidence: 57%
“…This model was based on partitioning coefficients (K D ) derived for P to Fe(III) oxyhydroxides associated with modern hydrothermal plumes. However, because the K D value for P sorption to Fe(III) oxyhydroxides diminishes in the presence of dissolved silica, later workers suggested that IF P/Fe ratios suggest that Archaean phosphate concentrations may not have been limiting (Konhauser et al, 2007a;Planavsky et al, 2010b).…”
Section: Iron Formations Primary Productivity and Atmospheric Oxygementioning
confidence: 99%